Study on Gear Elastic Deformation Modification based on Romax - Shi Ruonan; Zhang Ruiliang; Wang Tie; Wu Zhifei; Liu Yaqiong (Jixie chuandong)
An analysis of the gear micro modification is carried out by means of Romax software and a mathematical model of gear modification,and the methods of determining gear tooth surface modification amount are discussed.The research shows that,the gear modification design based on Romax can make the load of tooth surface uniformly distributed,reduce the transmission error and improve the bearing capacity and transmission quality of gear pair.